Three-dimensional exact solutions of homogeneous transversely isotropic coated structures under spherical contact. (April 2019) - Hou, P.F.; Zhang, W.H.; Chen, Jia-Yun
Abstract: Because of the large stress gradient in the coated structure and the more and more thin thickness of coating, it is too hard to guarantee the calculation accuracy by the commercial software in the design of the coated structure. In this case, a research work for an accurate and efficient calculation method for the coated structure is necessary and will contribute to the accurate design and quality promotion of the coated structure. In this paper, the three-dimensional solutions of homogeneous transversely isotropic coated structure under spherical contact loadings are derived based on the three-dimensional general solutions of the transversely isotropic material. The solutions are obtained in two cases including the smooth contact and the frictional contact. The numerical results show that this method has the good convergence, high accuracy, high efficiency and high stability. Based on this method, the optimal thickness of the coating and the interfacial stress between the coating and the substrate can be obtained accurately. Because the interfacial stress can result to the debonding failure of coated structures, a method for predicting interface security state with evaluation criteria for interfacial failure is proposed. The corresponding analysis will contribute to the strengthening design of the coated structure.